ESG Factor and Cost of Capital: What Do We Know? - Senna Dwi Renata Putri; Lauw Tjun Tjun (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study examines whether ESG factors and Cost of Capital (COC) have an influence on the increase in Firm Value (FV). The sample was selected based on predetermined criteria, which included all companies listed on the stock exchanges in each ASEAN member country between 2018 and 2022, obtained from the Refinitiv Eikon database. The total sample obtained for this study was 920 samples from 184 selected companies. ESG scores were obtained from the Refinitiv Eikon database, COC was measured using the Weighted Average Cost of Capital (WACC), and FV was measured using Tobin's Q. The results indicate that ESG has a positive influence on FV, while COC has no influence on FV. This study aims to analyze whether ESG and COC affect FV in companies listed on stock exchanges of ASEAN member countries.